2013 Proceedings IEEE INFOCOM 2013
DOI: 10.1109/infcom.2013.6567156
|View full text |Cite
|
Sign up to set email alerts
|

Economics of WiFi offloading: Trading delay for cellular capacity

Abstract: Cellular networks are facing severe traffic overloads due to the proliferation of smart handheld devices and traffichungry applications. A cost-effective and practical solution is to offload cellular data through WiFi. Recent theoretical and experimental studies show that a scheme, referred to as delayed WiFi offloading, can significantly save the cellular capacity by delaying users' data and exploiting mobility and thus increasing chance of meeting WiFi APs (Access Points). Despite a huge potential of WiFi of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 8 publications
1
73
0
Order By: Relevance
“…Utilities: The operator's utility function is given by U Operator (ε, δ) in (3). The utility function of D2D-Tx is given by U D2D−T x (R D ) in (8).…”
Section: D2d-tx As a Follower Takes Action In Stage II Stages I And mentioning
confidence: 99%
See 1 more Smart Citation
“…Utilities: The operator's utility function is given by U Operator (ε, δ) in (3). The utility function of D2D-Tx is given by U D2D−T x (R D ) in (8).…”
Section: D2d-tx As a Follower Takes Action In Stage II Stages I And mentioning
confidence: 99%
“…In [3], the economic benefits of delayed WiFi offloading were investigated, while in [4] the economic effects of useroriented delayed Wi-Fi offloading were studied in monopoly and duopoly market models. In [17], pricing strategies for both macro and femto cell operators in a cognitive femtocell network were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[11] have showed that offloading 3G traffic to WiFi can significantly benefit mobile ISPs. Other systems have demonstrated offloading's benefits for user experience [6], [8], [9]; other works demonstrate that WiFi offloading can benefit both ISPs and users [12] and even generate more revenue for ISPs [13].…”
Section: Related Workmentioning
confidence: 99%
“…WiFi offloading also has economic benefits, as a part of the cellular traffic is carried by low-cost WiFi networks. The economic performance is investigated in [17]. It is shown that the delayed offloading can yield great economic benefits compared to the on-the-spot offloading, in which 21% to 152% in the provider's revenue and 73% to 319% in the user's surplus (defined as the summation of users' net-utility) can be increased.…”
Section: Offloading Performancementioning
confidence: 99%